2020
DOI: 10.1029/2019ja026951
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Wave Growth Analysis of Whistler‐Mode Chorus Generation Regions Based on Coupled MHD and Advection Simulation of the Inner Magnetosphere

Abstract: We show the regions where nonlinear growth of whistler-mode chorus waves is preferred to occur in the inner magnetosphere. A global magnetohydrodynamics (MHD) simulation was used to obtain large-scale electric and magnetic fields under the southward interplanetary magnetic field condition. With the electric and magnetic fields obtained by the MHD simulation, we ran a comprehensive inner magnetosphere-ionosphere model to solve the evolution of phase space density of electrons. Hot electrons originating from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
(170 reference statements)
0
2
0
Order By: Relevance
“…The wave properties (e.g., intensity variations as a function of frequency at the Earth's magnetosphere by Yagitani et al, 2014 andat Saturn by Menietti et al, 2013) were characterized very well by the nonlinear growth theory. Not only the wave characteristics at a fixed location, Ebihara et al (2020) showed that the spatial development of the chorus wave generation in the Earth's magnetosphere can be reproduced by applying the nonlinear growth theory referred from the global magnetohydrodynamics and advection simulations in both fast and slow solar wind conditions. They showed that a wider spatial development of chorus generation distributing from in the premidnight-prenoon region outside the plasmapause in the fast solar wind case can be reproduced from a deep penetration of hot electrons into the inner region around up to L = 4 and a steep contraction of the plasmapause in the simulation results.…”
Section: Linear and Nonlinear Wave Growth Ratesmentioning
confidence: 99%
“…The wave properties (e.g., intensity variations as a function of frequency at the Earth's magnetosphere by Yagitani et al, 2014 andat Saturn by Menietti et al, 2013) were characterized very well by the nonlinear growth theory. Not only the wave characteristics at a fixed location, Ebihara et al (2020) showed that the spatial development of the chorus wave generation in the Earth's magnetosphere can be reproduced by applying the nonlinear growth theory referred from the global magnetohydrodynamics and advection simulations in both fast and slow solar wind conditions. They showed that a wider spatial development of chorus generation distributing from in the premidnight-prenoon region outside the plasmapause in the fast solar wind case can be reproduced from a deep penetration of hot electrons into the inner region around up to L = 4 and a steep contraction of the plasmapause in the simulation results.…”
Section: Linear and Nonlinear Wave Growth Ratesmentioning
confidence: 99%
“…The one-way coupling methodology has also been widely used in driving a kinetic RC model by a global magnetosphere model with a purpose of reproducing certain physical processes in the inner magnetosphere with a time-evolving global environment (Buzulukova et al, 2010;Ebihara et al, 2020;Ebihara & Tanaka, 2013;Hu et al, 2010;Zaharia et al, 2010;Zhang et al, 2008Zhang et al, , 2009. Unlike the two-way coupling, the RC model does not provide feedback to the global magnetosphere model.…”
Section: Driving the Inner Magnetosphere Models With The Global Magne...mentioning
confidence: 99%